FOREIGN ECONOMIC ACTIVITY: ESSENTIAL CHARACTERISTICS AND MANAGEMENT SYSTEM (Development Service Industry Management, 2023)
The management of Ukrainian enterprises in market conditions has always required their constant integration into the global economic space. This became especially relevant when Ukraine applied for membership in the European Union on February 28, 2022, thereby confirming its unconditional European integration. Under such circumstances, there is an urgent need for systematic theoretical and practical knowledge related to methods, processes of implementation and management of foreign economic activity of socio-economic systems under modern conditions. Foreign economic activity, unlike others, is extremely multifaceted. For a better understanding of the essence of this activity and the choice of the most effective methods and methods of its implementation, it is necessary, in our opinion, first of all to examine in detail the main definitions of the specified activity, as they in a concentrated form explain not only the essence itself, but also the structural content of the process of practical implementation of the definition. This study is dedicated to this.The interpretation of the definition of "foreign economic activity" in the legislative acts of Ukraine and the author's definitions of scientists were studied. The essence of this definition has been delineated at the level of process and business entities. The points of view of domestic and foreign scientists regarding the essence of the category "foreign economic activity of the enterprise" are summarized and the author's definition is formed, where the emphasis is placed on subjects of foreign economic activity. Priorities, levels, components, goals and objectives of the management system of foreign economic activity are determined. The management system of foreign economic activity is divided into the macro and micro levels of socio-economic systems in terms of essence and content. As a result, the author's definitions of the main categories of foreign economic activity related to the essence and process of its implementation were formed.
Keywords: foreign economic activity; foreign economic activity of the enterprise; management of foreign economic activity; management of foreign economic activity of the enterprise